Hereditary cerebral amyloid angiopathy mimicking CADASIL syndrome. (16th October 2021) - Psychogios, Klearchos; Xiromerisiou, Georgia; Kargiotis, Odysseas; Safouris, Apostolos; Fiolaki, Aidonio; Bonakis, Anastasios; Paraskevas, Georgios P.; Giannopoulos, Sotirios; Tsivgoulis, Georgios
Abstract: Background: Small vessel disease (SVD), and most specifically hereditary forms like CADASIL and cerebral amyloid angiopathy (hCAA), are conditions of increasing clinical importance. We report a rare case of hCAA in a Greek family that presented with a CADASIL clinical and neuroimaging phenotype. Methods: A 65‐year‐old man was admitted with recurrent transient episodes of right leg numbness. The patient's medical history started at the age of 50 years with depression and behavioral disorders. His family history was positive for stroke (father), dementia (father and brother), migraine (daughter) and depression (father and daughter). Results: Neurological examination disclosed anomic aphasia with severely impaired cognitive status, and brisk reflexes. Brain computed tomography and magnetic resonance imaging showed CADASIL‐like leukoencephalopathy (hyperintense lesions in bilateral temporopolar area, external capsule, thalami, centrum semiovale and superior frontal regions) with occipital calcifications and cerebral microbleeds. Screen for variants in NOTCH3 gene was negative. Exome sequencing revealed a novel pathogenic mutation for hCAA. Conclusions: We report a novel amyloid precursor protein mutation which results in a CADASIL‐like clinical phenotype (progressive cognitive and motor decline, stroke, migraine and behavioral disorders) and CADASIL‐leukoencephalopathy coupled with occipital calcifications. Earlier recognition and swift hCAA diagnosis may prompt rational preventive and potential disease‐modifying interventions. Abstract : We report a rare case of hereditary cerebral amyloid angiopathy (hCAA) associated with a novel mutation of the amyloid precursor protein in a Greek family that presented with a CADASIL clinical and neuroimaging phenotype. hCAA may mimic CADASIL clinical and typical neuroimaging findings, while occipital calcifications may serve as an essential neuroimaging marker for the differential diagnosis of these two conditions.